PENDAPATAN USAHA DAN PERSEDIAAN BAHAN BAKU INDUSTRI BAWANG GORENG (Studi Kasus Industri Bawang Goreng “Uda Saprudin”) - Herlena Bidi Astuti; Yesmawati Y; Linda Harta; Reswita R (Syarif Hidayatullah State Islamic University Jakarta, 2019)
Processing shallots into fried onions is one of the agro-industry businesses with the main raw material of shallots. The fried onion home industry is a downstreaming of agricultural commodities by providing added value from the raw materials of shallots, in the process of production competition the industry must conduct management that will produce raw materials to ensure obtaining products. The purpose of this study was to determine the operating income of fried onions and determine the management of raw materials in the